Plant genetic resources and climate change (CABI climate change series ;, 2014)
This new book Plant Genetic Resources and Climate Change contains 11 chapters summarizing perspectives on climatic change and how it might affect plant populations, and the expected impact on agriculture around the world. It presents some of the latest perspectives about how genetic resources can contribute to achieving food security under the challenge of a changing climate. It aims to highlight some key issues for plant genetic resources management, to demonstrate how perspectives have changed over two decades, and discuss some of the actual responses and developments.